Essential microeconomics - Riley, John G. (Cambridge : Cambridge University Press, 2012)
Essential Microeconomics is designed to help students deepen their understanding of the core theory of microeconomics. Unlike other texts, this book focuses on the most important ideas and does not attempt to be encyclopedic. Two-thirds of the textbook focuses on price theory. As well as taking a new look at standard equilibrium theory, there is extensive examination of equilibrium under uncertainty, the capital asset pricing model, and arbitrage pricing theory. Choice over time is given extensive coverage and includes a basic introduction to control theory. The final third of the book, on game theory, provides a comprehensive introduction to models with asymmetric information. Topics such as auctions, signaling and mechanism design are made accessible to students who have a basic rather than a deep understanding of mathematics. Examples and diagrams are used to illustrate issues as well as formal derivations.
Prices and optimization -- Consumers -- Equilibrium and efficiency in an exchange economy -- Firms -- General equilibrium -- Dynamic optimization -- Uncertainty -- Equilibrium in financial markets -- Strategy: games in which preferences and history are common knowledge -- Games with asymmetric information -- Incentive compatibility and mechanism design -- Auctions and public goods -- Appendix A. Mathematical foundations -- Appendix B. Mappings of vectors -- Appendix C. Optimization.
Title from publisher's bibliographic system (viewed on 18 Jul 2016).
Keywords: elektronické knihy; electronic books; Microeconomics